Evaluation of the CIPP Model of The Sewing Training Program - Akhadi, Dannie Yusfi; Shofwan, Imam (Journal of Nonformal Education, 2024)
BBPVP plays a role in organizing training and professional competency tests as an effort to improve the quality of human resources, but the implementation of competency tests carried out there are trainees who are not competent because they fail to master the standard competency units set. The purpose of this study is to describe the evaluation of the program in terms of (context, input, process, product). The research used a descriptive qualitative approach and the research data was obtained through observation of training activities, interviews with organisers, instructors and trainees, and documentation from institutional profile books, institutional websites and photographs of training activities. The results show that the context of the training programme is in line with the needs and objectives of the participants, namely their interests and professional needs. According to the input of the programme, the participants are of productive age (17-64 years old) and the participant are civil servants, graduates of fashion vocational training, who follow basic education and have a certificate of sewing expertise methodology. The curriculum is based on SKKNI and the source of funding comes from the state budget. The infrastructure includes machines, rooms and other supporting facilities. Process, schedule according to the total duration of 260 jp, instructor and participant activities are active in theory, discussion, practice and assignments. There is a weekly target as a strategy to adjust the programme to the plan set. By the end of the course, participants will be competent in sewing and will have increased self-confidence. Participants are declared passed when they have mastered the specified training competency units. In conclusion, the sewing training programme can be continued because it has been successful in providing competence to the trainees in terms of the CIPP aspects. The implication of this research is that when implementing training programmes, it is necessary to apply CIPP evaluation so that the implementation process can proceed in accordance with the planned programme objectives.